2015
DOI: 10.3390/ijms160817655
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of LAMP3 Is a Novel Biomarker of Poor Prognosis in Patients with Esophageal Squamous Cell Carcinoma

Abstract: Lysosomal-associated membrane protein 3 (LAMP3), identified as a molecular marker of mature dendritic cells, is one of the LAMP family members. Its expression was induced by hypoxia, and was associated with hypoxia mediated metastasis in breast and cervical cancers. However, epithelial expression of LAMP3 and its prognostic value in esophageal squamous cell carcinoma (ESCC) is still unknown. In the current study, mRNA expression of LAMP3 in 157 ESCC tissues and 50 adjacent normal tissues was detected by quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
(32 reference statements)
0
29
0
Order By: Relevance
“…LAMP3 expression is robustly induced in colorectal adenocarcinoma cells and depends on the stage of the disease (37). Abundant LAMP3 mRNA has been linked with poor prognoses in patients with stage-I or -II tumors in cervical cancer as well as ESCC (14,38,39). Therefore, the HAGLR/miR-143-5p/ LAMP3 axis plays a key role in EC progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAMP3 expression is robustly induced in colorectal adenocarcinoma cells and depends on the stage of the disease (37). Abundant LAMP3 mRNA has been linked with poor prognoses in patients with stage-I or -II tumors in cervical cancer as well as ESCC (14,38,39). Therefore, the HAGLR/miR-143-5p/ LAMP3 axis plays a key role in EC progression.…”
Section: Discussionmentioning
confidence: 99%
“…LAMP3 is up-regulated and shares an association with lymph node metastasis (LNM) in gastric cancer (13). Liao et al (14) found that LAMP3 was amplified in esophageal squamous cell carcinoma (ESCC) cells, and its expression could serve as a target to predict the prognosis of ESCC. Besides, Ni et al (15) found that microRNA (miR)-143 expression was down-regulated in ESCC cells and exerted inhibitory effects on the development of ESCC.…”
mentioning
confidence: 99%
“…In contrast to the constitutive expression of LAMP-1 and LAMP-2 in many cell types, LAMP-3 expression is regulated temporally and spatially, or is induced by hypoxic conditions. Overexpression of LAMP-3 is known to be associated with cancer metastasis ( Liao et al, 2015 ; Mujcic 2009 ; Nagelkerke et al, 2013 ). Recently, LAMP-3 was reported to be associated with modulation of autophagy and autophagy-mediated drug sensitivity ( Dominguez-Bautista et al, 2015 ; Nagelkerke et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…17 LAMP3 is highly expressed in differentiated and mature dendritic cells, 18 as well as many cancer cell types, including esophageal cancer, cervical cancer, and breast cancer. [12][13][14][15] Reportedly, LAMP3 has a number of diverse functions including hepatic lipid metabolism 19 and is associated with Bipolar disorder and Schizophrenia. 20 Recently, LAMP3 has been reported as a speci c tumor protein.…”
Section: Discussionmentioning
confidence: 99%